ChemInform Abstract: CH3NH3SnxPb1‐xBr3 Hybrid Perovskite Solid Solution: Synthesis, Structure, and Optical Properties. Issue 48 (December 2015) - Mancini, Alessandro; Quadrelli, Paolo; Milanese, Chiara; Patrini, Maddalena; Guizzetti, Giorgio; Malavasi, Lorenzo
Abstract: Single‐phase (MeNH3 )Snx Pb1‐x Br3 (x = 0‐1) solid solutions are precipitated from aqueous solutions of Pb(O‐Ac)2 and SnBr2, MeNH2, excess HBr, and H4 P2 O6 (100→46 °C).